“DUAS NOTAS CHEGAM PARA MIM. DOIS ACORDES REPETIDOS SEM FIM”: A constituição musical, midiática e identitária do rock gaúcho na década de 1980 - Nunes, Caroline Govari (Universidade do Vale do Rio dos Sinos, 2020)
This thesis aims to discuss the musical, media, and identity formation of “rock gaúcho” made in Porto Alegre, Rio Grande do Sul, Brazil, in the 1980s, considering its configurations as a scene and musical genre. First, I contextualize the 1980s, discussing mainly the phonographic industry and the media system. I draw a timeline in which I present some specifics events, such as the emergence of BRock (brazilian rock), the cultural effervescence of the Bom Fim neighborhood, festivals, radio stations, collection albums and local record companies in Porto Alegre. Then, I introduce the theories that support my thesis. My argument is that musical genre (BORN, 2016; LENA, 2012; BRACKETT, 2003; FRITH, 1996) is not only about sonorities aspects – but also social, economic, affective, etc. – and can be based on a music scene as well (STRAW, 2017; JANOTTI JR & PEREIRA DE SÁ, 2013; AMARAL et al, 2017). In other words, I also take into consideration the importance of the city in this context. To this end, I use some methodological approaches such as biographical research (ROSENTHAL, 2017), oral history (ROSA, 2007; PORTELLI, 1997) and documentary research (GIL, 2008). The memory theory (NORA, 1993, POLLAK, 1992) also works as a theoretical-methodological background. After this, I present the interviewees, with a short biography of each one of them, explaining the movements taken from the understanding of the methodological approach. Finally, I present my proposal of scene-based genre, discussing three important pillars to categorize “rock gaúcho”: 1) temporal and spatial issues, 2) aesthetics, attitude and sonorities and 3) media aspects. In addition to the categorization of “rock gaúcho”, I try to differentiate “rock gaúcho”, “BRock” (brazilian rock) and “rock made in Rio Grande do Sul”. The categorization proposed is related to a specific moment, of a generation of bands that appeared in a certain time and presents some peculiarities. Therefore, I discuss the musical identifications not only linked to sonorities, but also to the norms operated in a music scene, precisely in order to understand how communities can create genres in popular music.
Keywords: Cenas Musicais; Formações Identitárias; Gêneros Musicais; Mídia; Rock Gaúcho; Music scenes; Identity formations; Music genres; Media; Gaucho rock; ACCNPQ::Ciências Sociais Aplicadas::Comunicação